EASY WADIAH SAVINGS ANALYSIS OF CUSTOMER INTEREST AT BANK SYARIAH INDONESIA - Tasya Maharani; Nisrina Aulia; Siti Julaeha; Andi Amri (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
Bank Syariah Indonesia (BSI) is a financial institution that offers a variety of products, including savings with wadiah contracts (maintaining the authenticity of assets) known as "Easy Wadiah Savings". This savings product uses Wadiah Yad Damana contract in Rupiah currency with a zero-profit deposit system. There is no monthly management fee for these savings. You can also make free cash withdrawals at all BSI ATMs and Bank Mandir. In addition, all EDC Bank Mandir, EDC Indonesia, and EDC PRIMA networks are free of charge. In addition to mobile and internet banking, you can easily transact with ATM cards that you can use at all BSI ATMs, Bank Mandir, ATM Bersama, ATM Prima, ATM Link, and ATMs with the VISA logo. The account opening process can be done online through the BSI mobile application. This research is based on qualitative methods with descriptive explanations of data results. The data used is obtained from various references or secondary data, such as journals, articles, dissertations, and other sources. Research shows that customer interest in Easy Wadiah savings is increasing from year to year. The reason is, that the marketing strategy implemented by Bank Syariah Indonesia was successful and made many customers use Wadia contracts.